Perubahan Sosial dan Pendidikan - Mashuri; Jailani, M. Syahran; Isma, Asad (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
In the era of globalization and rapid technological advancement, socio-cultural changes occur rapidly, affecting various aspects of life, including education. This research aims to analyse how changes in values, norms, and social structures affect the education system and vice versa, and how education can act as an agent of socio-cultural change. The research method used is a literature study and secondary data analysis from various relevant sources. The results show that education has an important role in shaping individual character and personality to the demands of socio-cultural change. In addition, education has proven to be an important tool in facilitating social change, encouraging technological innovation, and strengthening social cohesion in the digital era. changes in curriculum, teaching methods, and educational policies are needed to face the challenges and needs of an ever-evolving society.